Spatiotemporal characterization of petroleum hydrocarbons and polychlorinated biphenyls in small craft harbour sediments in Nova Scotia, Canada. (April 2022) - Mora, Myriam; Walker, Tony R.; Willis, Rob
Abstract: Previous characterization of polycyclic aromatic hydrocarbons (PAHs) and metals has been conducted in small craft harbour (SCH) sediments in Nova Scotia, Canada, but petroleum hydrocarbons (PHCs) and polychlorinated biphenyls (PCBs) have not been spatiotemporally assessed. This study characterized the distribution of over 500 PHCs and PCBs samples in 31 SCHs sediments between 2000 and 2017. Federal and regional sediment quality guidelines were used to determine exceedances. Results showed exceedances for diesel and oil resembling PHCs, expected given their longer permanence in sediments and lower volatility. However, only 7% of the samples exceeded 500 ppm, threshold where benthic impairment is observed, showing low risk. PCBs do not pose high risk to biota since only six samples exceeded the higher effect level and 25% of them exceeded the lower effect one. Monitoring is recommended for SCHs with significant exceedances, as well as collectively assessing all contaminants characterized in SCHs. Graphical abstract: Unlabelled Image Highlights: Petroleum hydrocarbons and polychlorinated biphenyls (PCBs) were assessed in harbour sediments in Nova Scotia, Canada. Over 500 samples in 31 small craft harbour (SCH) sediments were characterized between 2000 and 2017. Federal and regional sediment quality guidelines were used to determine exceedances. Exceedances were for diesel and oil resembling hydrocarbons, but only 7% of samples exceeded 500 ppm threshold limits. PCBs do not pose high risk to biota (only 6 samples exceeded high effect and 25% of samples exceeded low effect levels).